(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
From the excessive military reprisal in the Gaza Strip to the accusation of genocide versus the State of Israel before the International Court of Justice (ICJ) ABSTRACT: The essay reflects on the total surprise of Hamas’attack on 7 October and the subsequent inhumanities on innocent civilians, but also on the obvious excesses of Tsahal’s retaliation (both on land and in the air), indiscriminately extended to areas populated by families, institutions and communities in the Gaza Strip, who are completely unrelated to the terrorist action just carried out in Israël. This is followed by an initial detailled analysis of the problems posed by the accusation of genocide against the state of Israël, following these events, brought at the International Court of Justice (ICJ) of United Nations by the republic of South Africa; with references to the procedural events following the order dated 26 January 2024, issued by the Court, with executive force, in the context of emergency measures. SOMMARIO - 1. Premessa. Qualche preoccupato testimone silenzioso - 2. Lo Stato di Israele nel precipizio aperto dall’attacco di Hamas - 3. Fra l’attacco di Hamas e l’invasione della Striscia di Gaza - 4. (intermezzo) ancora sull’inappagante giustizia del “divieto di aggressione” - 5. L’iniziativa del Sudafrica; sue caratteristiche valoriali - 6. L’atto introduttivo del giudizio. Tra forma e sostanza - 7. Natura e fondamento delle misure interdittive sollecitate dal Sudafrica - 8. Ostilità del gabinetto di guerra di Israele verso l’ordinanza della Corte dell’Aja - 9. (segue) Estensione dell’eccidio alla componente cristiana: suo significato razzista - 10. La paradossale pretesa di immunità giurisdizionale avanzata (ex post) da Israele - 11. (segue) Africa come visione. Il sogno di Mandela.